2022
DOI: 10.1186/s12974-022-02633-5
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin-A alleviates neuroinflammation against traumatic brain injury-induced microglial necroptosis by regulating Nrf-2/HO-1 pathway

Abstract: Background The microglia-mediated inflammatory response is a vital mechanism of secondary damage following traumatic brain injury (TBI), but the underlying mechanism of microglial activation is unclear. Methods Controlled cortical impact (CCI) was induced in adult male C57BL/6J mice, and glutamate was used to construct a classical in vitro injury model in the primary microglia. Microglial activation was determined by western blot and immunostaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…36 Moreover, the protective effects of fetuin A have also been attributed to a significant decrease in oxidative stress and restoration of anti-oxidative actions. 61 Based on the previous studies and the results of the present study, it may be proposed that the beneficial effects of fetuin A in sepsis-induced myocardial injury may be secondary to a decrease in inflammatory reactions and reduction in oxidative stress. Since fetuin A employed in the present study was derived from the fetal bovine serum (Sigma Aldrich, USA), therefore, fetuin A was not identical to the endogenous fetuin A of Swiss mice.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…36 Moreover, the protective effects of fetuin A have also been attributed to a significant decrease in oxidative stress and restoration of anti-oxidative actions. 61 Based on the previous studies and the results of the present study, it may be proposed that the beneficial effects of fetuin A in sepsis-induced myocardial injury may be secondary to a decrease in inflammatory reactions and reduction in oxidative stress. Since fetuin A employed in the present study was derived from the fetal bovine serum (Sigma Aldrich, USA), therefore, fetuin A was not identical to the endogenous fetuin A of Swiss mice.…”
Section: Discussionsupporting
confidence: 53%
“…Furthermore, it has also been reported that fetuin‐A supplementation significantly inhibits the IFN‐ℽ and endotoxin‐induced HMGB1 (late mediator) release in a concentration‐dependent manner by stimulating macrophages‐mediated phagocytic elimination of apoptotic cells 36 . Moreover, the protective effects of fetuin A have also been attributed to a significant decrease in oxidative stress and restoration of anti‐oxidative actions 61 . Based on the previous studies and the results of the present study, it may be proposed that the beneficial effects of fetuin A in sepsis‐induced myocardial injury may be secondary to a decrease in inflammatory reactions and reduction in oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…Another aspect of TBI pathogenesis is increased neuroinflammation postinjury . It has been shown that the microglia undergo necroptosis in TBI, resulting in expanded patient inflammatory profiles. Though a direct correlation between EVs and the neuroinflammatory cascade in TBI is underexplored, a correlation is suggestive, given the immunomodulatory roles of EVs. Indeed plasma-derived EVs from warfighters display increased levels of cytokines like IL-10, which positively correlated to poor sleep quality in TBI patients .…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
“…In this study, we first observed that CASK silencing in human CHME3 microglia significantly attenuates H 2 O 2 -induced cell death. Depending on the stress stimuli and cellular contexts, oxidative stress may lead to microglial apoptosis [ 44 ], parthanatos [ 45 ], or necroptosis [ 46 , 47 ]. Our study shows that H 2 O 2 -induced cell death is abrogated by the PARP-1 inhibitor olaparib, suggesting that the CHME3 cells undergo parthanatos under H 2 O 2 treatment.…”
Section: Discussionmentioning
confidence: 99%